Cost estimates for flood resilience and protection strategies in New York City. (5th August 2013) - Aerts, Jeroen C.J.H.; Botzen, W.J. Wouter; de Moel, Hans; Bowman, Malcolm
Abstract : In the aftermaths of Hurricanes Irene, in 2011, and Sandy, in 2012, New York City has come to recognize the critical need to better prepare for future storm surges and to anticipate future trends, such as climate change and socio‐economic developments. The research presented in this report assesses the costs of six different flood management strategies to anticipate long‐term challenges the City will face. The proposed strategies vary from increasing resilience by upgrading building codes and introducing small scale protection measures, to creating green infrastructure as buffer zones and large protective engineering works such as storm surge barriers. The initial investment costs of alternative strategies vary between 11.6 and 23.8 bn, maximally. We show that a hybrid solution, combining protection of critical infrastructure and resilience measures that can be upgraded over time, is less expensive. However, with increasing risk in the future, storm surge barriers may become cost‐effective, as they can provide protection to the largest areas in both New York and New Jersey.